Participatory networks in surveillance and prevention of dengue haemorrhagic fever: case study of Child-daycare Development Center, Khlonghae Subdistrict, Hat Yai District, Songkhla Province - Wattanapurk, Siriporn; Perngmark, Pajongsil; Suwanrat, Ratnaris; Yodkaew, Supachoke (Disease Control Journal, 2024)
In 2019, an epidemic of dengue haemorrhagic fever (DHF) occurred at Bannongnaikhui community and had spread to urban areas including the Bannongnaikhui elementary school. Bannongnaikhui Child-Daycare Development Center located within the same boundary of the elementary school. As a result, the Child-Daycare Development Center seemed to become high-risk zone for the third wave of DHF epidemic. This study aimed to develop guidelines applying the concept of network involvement and participation in monitoring and preventing a new wave of DHF spread. The action research was performed including 4 steps: situation analysis and needs assessment, planning, implementation, and evaluation. Primary data were collected by interviewing stakeholders from many sectors along with participatory observation of risky physical environments. Secondary data were analyzed from the questionnaire and the assessment. The study results found that network partners which included officials or personnel of public health agencies, personnel of the child-daycare development center, personnel of the school, village health volunteer leaders, community representatives, and municipal officials worked in a cooperative effort by applying the Google Map application to proactively screen and locate the patients. Besides, jointly assess physical risk areas and create innovations including “Bergamot spray” and “Cyclical rule” were applied to prevent the spread of the disease at the child-daycare development center. In conclusion, the participation of network partners is the key to success in monitoring and preventing disease from spreading DHF epidemic in high-risk areas. This concept should therefore be applied to other high-risk areas with similar contexts.